2008
DOI: 10.1371/journal.pone.0002494
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood Treatment in a Mouse Model of ALS: Optimization of Cell Dose

Abstract: BackgroundAmyotrophic Lateral Sclerosis (ALS) is a multicausal disease characterized by motor neuron degeneration in the spinal cord and brain. Cell therapy may be a promising new treatment for this devastating disorder. We recently showed that a single low dose (106 cells) of mononuclear human umbilical cord blood (MNC hUCB) cells administered intravenously to G93A mice delayed symptom progression and modestly prolonged lifespan. The aim of this pre-clinical translation study is to optimize the dose of MNC hU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 41 publications
4
63
0
Order By: Relevance
“…In particular, the analysis of the levels of cytokines measured in vehicletreated ALS mice and in ALS mice receiving cells suggested that transplantation may favor the maintenance of Th-2 innate adaptive immune response by delaying the switch to the Th1-mediated pro -inflammatory response and therefore attenuating the clinical progression (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the analysis of the levels of cytokines measured in vehicletreated ALS mice and in ALS mice receiving cells suggested that transplantation may favor the maintenance of Th-2 innate adaptive immune response by delaying the switch to the Th1-mediated pro -inflammatory response and therefore attenuating the clinical progression (9).…”
Section: Resultsmentioning
confidence: 99%
“…However, the lack of apparent cell migration to the side of injury (ventral horn of the Wr cervical spinal cord) and the absence of their differentiation toward motor neurons did not allow us to speculate that there is a cell replacement by SkmSCs. Whereas other MSC transplantation studies in ALS animal models demonstrate a motor efficacy improvement without grafts replacement, we have chosen to focus our investigation on the evaluation of the SkmSC pharmacological effects (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the earliest studies, a survival benefit was demonstrated in irradiated SOD1-G93A mice treated with human umbilical cord blood [93,94]. Follow-up studies also showed that transplanted human cord blood along with immunosuppression with cyclosporine delayed disease progression and that the transplanted cells were detected in the brain and spinal cord [25,26]. From these beginnings arose many strategies to harness the potential of stem cells for ALS.…”
Section: Transitioning From Early Preclinical Studies To Current Tranmentioning
confidence: 99%
“…In a recent study, it was shown that a single low dose (10 6 cells) of human umbilical cord blood-derived mononuclear cells (hUCBMNCs) administered intravenously to G93A mice with amyotrophic lateral sclerosis delayed symptom progression and modestly prolonged lifespan (6). It has been shown that human umbilical cord blood contains abundant with hematopoietic stem cells, mesenchymal stem cells, and endothelial progenitor cells that are able to differentiate into nerve cells and endothelial cells (7 -10).…”
Section: Introductionmentioning
confidence: 99%